The Effectiveness of Interprofessional Collaboration Practice to Reduce The Risk of Stunting: An Integrative Review - Sulistyaningsih Sulistyaningsih; Resya Aprillia; Lulu Annisa; Cindy Putri Febrianti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Stunting is a chronic nutritional problem that results in the height of children under five years old being inappropriate for their age or causing growth delay of children. Success in Interprofessional Collaboration Practice (IPC) in reducing the risk of stunting can be assessed from several indicators, including Framework WHO and IPEC. This review aimed to synthesize the existing evidence regarding the effectiveness of IPC in an effort to reduce the risk of stunting. The integrative review adapts Reporting Flowchart from Bulmer Smith et al., 2009. Pubmed, Proquest, and Grey literature were used as the databases and accessed through the Google Scholar search engine by filtering articles published from 2017-2022. There were 10 of the 1,019 articles screened by inclusion and exclusion criteria in this review. Critical Appraisal uses the tools of The Joanna Briggs Institute (JBI). This review found that several indicators of IPC success in reducing stunting risk include roles or responsibilities, interpersonal communication, values and ethics, work culture, environment, institutional or agency support, and IPC results. All indicators have their interrelated roles, if collaboration practices are not carried out properly, the results obtained are less than optimal. The IPC method of reducing the risk of stunting focuses more on knowledge and health education promotions. IPC is expected to be one of the solutions that can be considered to help reduce the risk of stunting in toddlers and increase the attention of agencies/institutions with authority to provide ultimate support. Abstrak: Stunting merupakan masalah gizi kronis yang mengakibatkan tinggi badan anak di bawah lima tahun tidak sesuai dengan usianya atau pertumbuhan anak melambat. Keberhasilan Interprofessional Colaboration Practice (IPC) dalam penurunan resiko kejadian stunting dapat dinilai dari beberapa indikator, Framework WHO dan IPEC. Penelitian ini bertujuan untuk mensintesis bukti yang ada mengenai efektivitas IPC dalam upaya penurunan risiko stunting. Metode integrative review ini mengadaptasi Reporting Flowchart dari Bulmer Smith et al., 2009. Database yang digunakan yaitu 3 database yaitu Pubmed, Proquest dan Google Scholar dengan menyaring artikel yang terbit mulai tahun 2017-2022. Tinjauan ini berhasil menemukan 10 artikel dari 1.019 artikel yang sudah disaring dengan kriteria inklusi dan eksklusi. Critical Appraisal menggunakan tools The Joanna Briggs Institute (JBI). Tinjauan ini menemukan bahwa beberapa indikator dari keberhasilan IPC dalam penurunan risiko stunting diantaranya peran atau tanggung jawab, komunikasi interpersonal, nilai dan etika, budaya kerja, lingkungan, dukungan institusi atau instansi dan hasil IPC. Seluruh indikator memiliki peran tersendiri yang saling berkaitan, jika praktik kolaborasi tidak dijalankan dengan baik maka hasil yang dapatkan kurang maksimal. Metode IPC pada penurunan risiko stunting lebih berfokus pada promotif terkait pengetahuan dan pendidikan kesehatan. IPC diharapkan menjadi salah satu solusi yang dapat dipertimbangkan untuk membantu menurunkan risiko stunting pada balita dan meningkatkan perhatian instansi/ institusi yang memiliki wewenang untuk memberikan dukungan secara maksimal.